ORGANIC RANKINE CYCLE ASSOCIATED WITH AN ABSORPTION CHILLER FOR BIOMASS APPLICATIONS - Sotomonte, C. A. R.; Ribeiro, S.; Oliveira, E.; Lora, E. E. S.; Venturini, O. J. (Revista de Engenharia Térmica, 2011)
The main goal of this work is to develop a calculation process, based on the second law of thermodynamic, for evaluating the potential of a small Organic Rankine Cycle (ORC) cogeneration (electrical and cooling power) plant using biomass as fuel. Two different configurations and several organic working fluids are presented and assessed. A mathematical model has been developed to find thermodynamically suitable fluids for ORC in biomass cogeneration plants. The main results show that, the family of alkylbenzenes has higher exergetic efficiencies found to be around 16% almost 5 percent higher efficiency than the cycles that use siloxanes as working fluids; in spite of their lower cooling power capacity. The results demonstrate that the cycle efficiency is more dependent on the thermodynamic properties of the working fluids than on the system configuration.